Human rights and social justice in Quranic contexts: a global trend - A.N., Andri Nirwana; Mahmudulhassan, Mahmudulhassan; Marshal, Fahmi Dolles; Muthoifin, Muthoifin; Fadli, Nazar (Legality : Jurnal Ilmiah Hukum, 2024)
Scholarly interest in the study of social justice and human rights in Quranic contexts has increased in light of global conversations about ethical governance, equality, and justice. To fully comprehend how Islamic texts contribute to current human rights discourses, this study aims to present a bibliometric analysis of key trends, authors, and themes in the literature surrounding these problems. Using R/R-Studio, Vosviewer, Microsoft Excel, and a Boolean search on Scopus, data from 2019 to 2024 is analysed to identify important trends, authors, affiliations, and thematic developments within these interconnected disciplines. The results show a wide range of research interests and substantial publication activity with noteworthy contributions from different nations and institutions. Network visualisations highlight the transdisciplinary nature of the discourse by illuminating the relationships and co-occurrences of important terms. This study offers important insights into the development of scholarly research on these important subjects, laying the groundwork for further research and educating practitioners and politicians on the relationship between social justice, legal doctrine, and religious texts.